Patterns in Rainfall Cessations and Public Policy Implications on Sustainable Food Security Under Distinct Imo Agro-Climatic Zones - Ikpong Umo; Ambrose Abaneme; Ifeanyi Ukwe; Christian Ogu (American Journal of Biological and Environmental Statistics, 2026)
The collective efforts in tackling climate change impacts have gained popularity at the global level, but regional and local agro-land users tend to suffer failures due to limited capacity to adapt to the uncertainties in annual rainfall indices of onset, growing season, and cessation. This study evaluates the space-time dimension of uncertainties in rainfall cessations and its implication on crop yield and food security in Imo State. The state was stratified into three agro-land zones. Rainfall data were extracted from secondary sources using gridded method from 19981 to 2023 (43) climatic years and analyzed using diverse descriptive and inferential statistical tools. The results reveal that Imo East recorded the highest mean value of 321.232 mm, while Imo West recorded the highest standard deviation of 13.898 mm. The earliest rainfall cessation is recorded in Imo on 21 st October. 1998, while late cessation occurs homogenously in Imo West and Imo East on 26 th December, 1990climatic year. The time series evaluation offers a uniform positive trend pattern but at distinct rates across the sampled agro-climatic zones. The regression models of the trend dimensions reveal that Imo North exhibits a positive highest predictive equation of 0.288x+311.8 and a corresponding highest co-efficient of 0.077. ANOVA test of the proportion variance in uncertainties in rainfall cessation among the agro-climatic zones led to a conclusion that the uncertainties in rainfall cessations in Imo State are independent of geographic location. This study recommends for the urgent increased capacity building through farmers’ education and sustainable financing of multiple land use practices for improved crop yield per farmland and food security in Imo State.